Selection for muscling in Durocs - J D Wheat; Donald H Kropf; P Na-Lampang; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1978)
Select line pigs were compared with those in the control line for growth patterns, production traits, and carcass quality. Heritability and genetic correlations were calculated for certain production and carcass traits after five generations of selection.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Muscling; Durocs